2004
DOI: 10.1007/s10735-004-1746-0
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the expression of tight and adherens junction-associated proteins during maturation of neonatal pancreatic islets in vitro

Abstract: Cell-cell contacts mediated by intercellular junctions are crucial for proper insulin secretion in the endocrine pancreas. The biochemical composition of the intercellular junctions in this organ and the role of junctional proteins in endocrine pancreatic dysfunctions are still unclear. In this study, we investigated the expression and cellular location of junctional and cytoskeletal proteins in cultured neonatal rat pancreatic islets. Neonatal B-cells had an impaired insulin secretion compared to adult cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…Upregulation of occluding and ZO-1 has been shown during the maturation of neonatal pancreatic islet cells in vitro. Gap junctions have been involved in regulation of insulin secretion [4]. However, besides being involved in normal islet intercellular communication, it is likely that TJs also provide adaptive mechanisms intended to seal and protect islet microdomains against sudden perturbations in extracellular environment.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Upregulation of occluding and ZO-1 has been shown during the maturation of neonatal pancreatic islet cells in vitro. Gap junctions have been involved in regulation of insulin secretion [4]. However, besides being involved in normal islet intercellular communication, it is likely that TJs also provide adaptive mechanisms intended to seal and protect islet microdomains against sudden perturbations in extracellular environment.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Before being used, each new batch of Cx36 and Cx43 antibodies was first tested for its specificity in rat brain and heart homogenates, respectively. To ensure equal amounts of protein were loaded in all lanes, the membranes were reprobed with an antibody against the cytoskeletal protein vinculin (Sigma), used herein as an internal standard, because it has been shown that its expression does not change over culturing in neonatal islet cells (Collares-Buzato et al 2004). …”
Section: Western Blotmentioning
confidence: 99%
“…Over-expression of dominant negative hepatocyte nuclear factor-1 in mouse β-cells (the gene responsible for type 3 MODY) results in abnormal islet architecture, down-regulation of E-cadherin and reduced insulin secretion [14,15]. Similarly, the MIN6 cell line sub-clone (C3) has been identified with reduced glucose evoked insulin secretion and down-regulated E-cadherin expression [16], whilst in rat pancreatic islets, increased expression of the adherens proteins α-and β-catenin is correlated with increased glucose evoked insulin secretion [17]. It is clear that E-cadherin not only plays an important role in islet development but also in the continued function of the islet in terms of glucose responsiveness and insulin secretion.…”
Section: Introductionmentioning
confidence: 99%